Fractal scan strategies for selective laser melting of ‘unweldable’ nickel superalloys - Catchpole-Smith, S.; Aboulkhair, N.; Parry, L.; Tuck, C.; Ashcroft, Ian; Clare, A. (Elsevier, 2017)
The high thermal gradients experienced during manufacture via selective laser melting commonly result in cracking of high γ/γ′ Nickel based superalloys. Such defects cannot be tolerated in applications where component integrity is of paramount importance. To overcome this, many industrial practitioners make use of hot isostatic pressing to ‘heal’ these defects. The possibility of such defects re-opening during the component life necessitates optimisation of SLM processing parameters in order to produce the highest bulk density and integrity in the as-built state. In this paper, novel fractal scanning strategies based upon mathematical fill curves, namely the Hilbert and Peano-Gosper curve, are explored in which the use of short vector length scans, in the order of 100 μm, is used as a method of reducing residual stresses. The effect on cracking observed in CM247LC superalloy samples was analysed using image processing, comparing the novel fractal scan strategies to more conventional ‘island’ scans. Scanning electron microscopy and energy dispersive X-ray spectroscopy was utilised to determine the cracking mechanisms. Results show that cracking occurs via two mechanisms, solidification and liquation, with a strong dependence on the laser scan vectors. Through the use of fractal scan strategies, bulk density can be increased by 2 ± 0.7% when compared to the ‘island’ scanning, demonstrating the potential of fractal scan strategies in the manufacture of typically ‘unweldable’ nickel superalloys.